Canada's global health role: supporting equity and global citizenship as a middle power. Issue 10131 (28th April 2018) - Nixon, Stephanie A; Lee, Kelley; Bhutta, Zulfiqar A; Blanchard, James; Haddad, Slim; Hoffman, Steven J; Tugwell, Peter
Summary: Canada's history of nation building, combined with its status as a so-called middle power in international affairs, has been translated into an approach to global health that is focused on equity and global citizenship. Canada has often aspired to be a socially progressive force abroad, using alliance building and collective action to exert influence beyond that expected from a country with moderate financial and military resources. Conversely, when Canada has primarily used economic self-interest to define its global role, the country's perceived leadership in global health has diminished. Current Prime Minister Justin Trudeau's Liberal federal government has signalled a return to progressive values, driven by appreciation for diversity, equality, and Canada's responsibility to be a good global citizen. However, poor coordination of efforts, limited funding, and the unaddressed legacy of Canada's colonisation of Indigenous peoples weaken the potential for Canadians to make meaningful contributions to improvement of global health equity. Amid increased nationalism and uncertainty towards multilateral commitments by some major powers in the world, the Canadian federal government has a clear opportunity to convert its commitments to equity and global citizenship into stronger leadership on the global stage. Such leadership will require the translation of aspirational messages about health equity and inclusion into concrete action at home and internationally.